ANALYSIS OF INDONESIA'S GOOD NEIGHBOR POLICY TOWARDS INCREASING THE INTENSITY OF INTRA SOUTHEAST ASIA FOREIGN TRADE - Faridatuz Zahro Dhiyaul Auliyah; Intan Kinanthi Damarin Tyas; Khoirul Amin (Jurnal Indonesia Sosial Sains, 2025)
The Good Neighbor Policy was initiated by the 4th President Abdurrahman Wahid during his tenure as President of Indonesia from 1999 to 2001 and recognized as a formal strategy by President Joko Widodo in 2014. Through the regional trade theory of Good Neighbor Policy, its participation in the ASEAN Free Trade Area (AFTA) encouraged the elimination of tariffs among ASEAN members. While in the Asia-Pacific Economic Cooperation (APEC) it focused on liberalizing trade, investment, and strengthening regional connectivity. Furthermore, the Regional Comprehensive Economic Partnership (RCEP) can expand market access and supply chain integration. Through Foreign Policy theory, it provides a systematic analytical framework to understand how Indonesia's Good Neighbor Policy contributes to increased foreign trade. By analyzing inputs, processes, and outputs, this research can identify factors that influence the success of the policy in improving trade relations with neighboring countries. Therefore, this study aims to analyze more deeply about Indonesia's use of Good Neighbor Policy (GNP) in strengthening trade and economic relations with ASEAN countries, creating regional stability and growth and increasing economic benefits. This research uses a qualitative approach analytical descriptive method through literature study.